THE MAN AT THE SELF-PAINTED WINDOW - Edi Yuwono; Stefanny Irawan (Institute of Research and Community Outreach - Petra Christian University, 2017)
This creative project is an autobiographical novel that tells the story of Hero Widjaja, a Chinese Indonesian man who embarks on his journey to Hong Kong, Macau, and Mainland China to find his true identity. Having raised in a pretty conservative Chinese Indonesian family background, Hero learns that there is an unfinished business in finding his identity as a Chinese Indonesian man. His parents unconsciously indoctrinate him to identify himself just like Mainland Chinese people. On the other hand, Hero surely does not have Chinese citizenship or even speak Mandarin. One morning, his father offers him a free trip to visit his relatives in Mainland China. Keeping the desire to find his true identity, Hero decides to take the trip and prove it himself whether he is eligible to regard himself as Chinese. I decide to use Erikson’s stages of psychosocial development to identify Hero’s identity crisis. This theory aims to help me create problems and believable characterization for my characters to represent the identity crisis that Chinese Indonesian people may have in real life. As for the genre, I decide to choose biographical novel as the genre of my creative work. I mix my personal family experiences as a Chinese Indonesian man with fictional elements so that I can still catch my readers’ attention from the beginning to the end.